Cultural Competence and Cultural Compensatory Mechanisms in Binational Households - Cross, Samantha N.N. and Gilly, Mary C. (Journal of Marketing, 2014)
Although it is well-known that the U.S. population is increasingly culturally diverse, cultural diversity within U.S. households is less recognized. This study investigates the effects of cultural dynamics on decision roles and influence within the binational household. In particular, the authors study households in which one spouse is from the United States and the other is an immigrant. The analysis uses survey data and in-depth interviews. Cultural competence (i.e., knowledge of country of residence) as a source of expert power and as a form of cultural capital in family decision making emerge as overarching themes. The authors also find that one family member may engage in cultural compensatory mechanisms in consumption in response to the immigrant family member's sacrifices (i.e., moving to the United States). The authors close with a discussion of the implications for family decision-making theory, marketers, and society.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUwOS9qbS4xMS4wMzEw